(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
In the article, the impact of political institutions on the further establishment of democratic principles in New Uzbekistan and increasing the activity of citizens, raising their legal and political awareness, is scientifically covered, and a number of suggestions and recommendations are given.